THE ROLE OF SCIENTIFIC BOOKS AND FILMS IN ENHANCING ENGLISH LEARNING FOR A2 LEARNERS - Khusanova, Farangiz (MMIT Proceedings, 2023)
This study aimed to investigate the effectiveness of using scientific books and films as a tool to enhance the English language learning of A2 level learners. The study employed a quantitative research design, where a pre-test and post-test were administered to measure the participants' language proficiency before and after the intervention. The participants were 50 A2 level learners selected from a language center in Tashkent, Uzbekistan. The data were analyzed using paired t-test and descriptive statistics. The results showed a significant improvement in the participants' English language proficiency after using scientific books and films. The findings suggest that incorporating scientific books and films in language learning can be an effective and engaging approach to improve the language proficiency of A2 level learners.